2021
DOI: 10.3389/fcell.2021.636321
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Cytochrome P450-1b1 Increases Susceptibility of Pressure-Induced Axonopathy in the Murine Retinal Projection

Abstract: Mutations in the cytochrome P450-1B1 (Cyp1b1) gene is a common genetic predisposition associated with various human glaucomas, most prominently in primary congenital glaucoma (PCG). The role of Cyp1b1 in the eye is largely unknown, however, its absence appears to drive the maldevelopment of anterior eye structures responsible for aqueous fluid drainage in murine models. Nevertheless, vision loss in glaucoma ultimately results from the structural and functional loss of retinal ganglion cells (RGCs). Cyp1b1’s in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…In mouse models, however, the deficiency of Cyp1b1 appears to be involved in maldevelopment of the anterior eye structures, which regulate the aqueous humour outflow pathway [ 36 , 123 , 124 ]. Since glaucoma eventually results from defects in the RGCs due to increased sensitivity to IOP changes, the influence of Cyp1b1 on the development of RGCs under normal and stressed conditions, such as elevated ocular pressure, was investigated [ 123 ]. It was found that where deletion of Cyp1b1 alone is insufficent to demonstrate glaucomatous features in mice, it may increase the susciptibility of RGCs to degeneration in reponse to elevated IOP [ 123 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In mouse models, however, the deficiency of Cyp1b1 appears to be involved in maldevelopment of the anterior eye structures, which regulate the aqueous humour outflow pathway [ 36 , 123 , 124 ]. Since glaucoma eventually results from defects in the RGCs due to increased sensitivity to IOP changes, the influence of Cyp1b1 on the development of RGCs under normal and stressed conditions, such as elevated ocular pressure, was investigated [ 123 ]. It was found that where deletion of Cyp1b1 alone is insufficent to demonstrate glaucomatous features in mice, it may increase the susciptibility of RGCs to degeneration in reponse to elevated IOP [ 123 ].…”
Section: Discussionsupporting
confidence: 81%
“…The precise function of CYP1B1 in the human eye and CG development is still unknown. In mouse models, however, the deficiency of Cyp1b1 appears to be involved in maldevelopment of the anterior eye structures, which regulate the aqueous humour outflow pathway [ 36 , 123 , 124 ]. Since glaucoma eventually results from defects in the RGCs due to increased sensitivity to IOP changes, the influence of Cyp1b1 on the development of RGCs under normal and stressed conditions, such as elevated ocular pressure, was investigated [ 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies by Amirmokhtari et al demonstrate that naive Cyp1b1-KO mice develop an anatomically intact retinal projection without overt signs of glaucomatous pathology [62]. However, following pressure elevation, accelerated degradation of axonal transport from the retina to the superior colliculus and altered morphology of the nodes of Ranvier and adjacent paranodes in the optic nerves were observed [62].…”
Section: Cyp1b1 Animal Modelsmentioning
confidence: 99%
“…So far, whether Cyp1b1 −/− causes IOP abnormalities and glaucomatous phenotypes in mouse models is controversial. Amirmokhtari et al reported that IOP in Cyp1b1 −/− mice was within the physiological range (10–15 mmHg) [ 134 ]. Compared with WT mice, Cyp1b1 −/− in mice was insufficient to induce murine glaucomatous pathology but increased susceptibility to abnormal IOP-induced retinal axon damage [ 134 ].…”
Section: Animal Models Related To Pcgmentioning
confidence: 99%